2020
DOI: 10.1016/j.sjbs.2020.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing azithromycin antibacterial activity by encapsulation in liposomes/liposomal-N-acetylcysteine formulations against resistant clinical strains of Escherichia coli

Abstract: E. coli is an Enterobacteriaceae that could develop resistance to various antibiotics and become a multi-drug resistant (MDR) bacterium. Options for treating MDR E. coli are limited and the pipeline is somewhat dry when it comes to antibiotics for MDR bacteria, so we aimed to explore more options to help in treating MDR E. coli . The purpose of this study is to examine the synergistic effect of a liposomal formulations of co-encaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
3
11
0
1
Order By: Relevance
“…Analyzing the MIC of the different formulations showed that the AZM-ZnONP formulation was very effective against both MRSA and E. coli and the MIC was reduced markedly compared to each of them when used alone. Similarly, Aljihani, et al [48] reported that liposomal AZM and liposomal AZM/N-acetyl cysteine markedly improved the MIC of AZM against E. coli. Another study showed that AZM nanoparticles produced the same inhibitory effect against E. coli at an eight times lower concentration compared to free AZM [70].…”
Section: In Vitro and In Vivo Antibacterial Activitiesmentioning
confidence: 87%
See 1 more Smart Citation
“…Analyzing the MIC of the different formulations showed that the AZM-ZnONP formulation was very effective against both MRSA and E. coli and the MIC was reduced markedly compared to each of them when used alone. Similarly, Aljihani, et al [48] reported that liposomal AZM and liposomal AZM/N-acetyl cysteine markedly improved the MIC of AZM against E. coli. Another study showed that AZM nanoparticles produced the same inhibitory effect against E. coli at an eight times lower concentration compared to free AZM [70].…”
Section: In Vitro and In Vivo Antibacterial Activitiesmentioning
confidence: 87%
“…The MICs of the AZM, ZnO, and AZM-loaded ZnONPs were determined against the clinical MRSA and E. coli isolates using the broth dilution technique [48]. Firstly, different formulations were serially diluted in a 96-well plate in Mueller-Hinton broth starting at a concentration of 200 µg/mL.…”
Section: Determination Of the Minimal Inhibitory Concentration (Mic)mentioning
confidence: 99%
“…RUT starts to lose its weight from 45 °C, but when it was formulated as liposomes, degradation starts at 225 °C, which ensures the stability of RUT in the liposomal vesicle. Stability of other excipients such as HSPC, TPGS, and cholesterol was also observed to be improved as before formulating they were showing a sharp decline in weight loss, but when it was formulated as RUT-LIPO, the weight loss was observed in a progressive manner at a wide range of temperatures (Figure C) …”
Section: Discussionmentioning
confidence: 92%
“… 130 A liposomal formulation of co-encapsulated azithromycin and N-acetylcysteine has been demonstrated to have a synergistic effect against bacterial strains. 131 The high cellular membrane permeability and targeting accuracy associated with such a delivery system illuminates a potential implication for the co-formulation strategy of N-acetylcysteine with antiviral drug.…”
Section: Discussionmentioning
confidence: 99%